POR QUE FALAR DE TEORIA ANTROPOLÓGICA CLÁSSICA NO CAMPO ATUAL DA ALIMENTAÇÃO? - Madel Therezinha Luz (Universidade do Estado do Rio de Janeiro, 2013)
We may ask ourselves after reading this dense, coherent and reasonably long argumentation in the article "Estruturalfuncionalismoantropológico e comensalidade: brevesconsiderações sobre a mudança social" (Anthropologicalstructural functionalism and commensality: brief reflectionson social change) by César Sabino and Maria Cláudia da VeigaSoares de Carvalho, if it still makes sense to talk about thestructural-functionalist approach, in the Social Sciences, asa model, theory, or method of analysis. Especially when readin the works of the founding fathers of anthropology and thevaried methodological and theoretical currents that, in thesecond half of the twentieth century, have been brought forthin anthropology, but also in Sociology, Politics, and finally(after the 1970s), in this extensive disciplinary field known as Social Communication.